The Message and Meaning on Short Animation Film "Surat Untuk Jakarta" - Prayogo, Matheus; Saidi, Acep Iwan; Murwonugroho, Wegig (VCD, 2019)
Jakarta is the center of business and government in Indonesian Republic that have population density about 15.000 citizen per kilometer. Jakarta have many major problem like different political view, high population density, traffic jam, increase of waste product, air population, etc. “Surat Untuk Jakarta” Animation short is about condition in Jakarta from day to night. For about two minutes, the winner of the Best Animation Category in Festival Film Indonesia show us about the architecture in Jakarta in exquisites 2D animation media. Despite of the success for gaining many award like “Best Picture Hellofest 2016”, this film just show the sequence of Jakarta. We can see the iconic building like Monumen National, Dirgantara Statue, Istiqlal Mosque, etc. But the problem is, there is no narrator that tell us what’s going on there. The shot change to another shot, but just segmented people that know the meaning and message of this film. This research purpose is to analyze the meaning and message of “Surat Untuk Jakarta” with semiotic metodolgy. The conclusion of this research is with visual element that have no narrator makes the meaning and the responds to target audience ineffective. The conclusion we have is this film is about the complexity of Jakarta, there are too many social gap in Jakarta, and we still need more pluralism in this city.